Assessing the Effectiveness of a Game-Based Method for Enhancing Kangkang Jump Skills in Students - Indah, Sri; Hadiana, Oman (LP3M, Universitas Muhammadiyah Kendari, 2024)
The kangkang jump is one of the basic movements in artistic gymnastics, which is the primary focus of this research. Observations conducted at school revealed that the material related to the kangkang jump was not delivered effectively by the teacher due to inadequate facilities required for the learning process. As a result, students exhibited poor kangkang jumping skills, stiff movements, and a lack of confidence due to fear of failure. This study aims to improve students' kangkang jumping skills through a game-based approach. The research employed an experimental method with a one-group pretest-posttest design. The population included all 140 students in grade V at SDN 2 Ciherang, Kadugede District, for the 2023/2024 academic year, with a research sample of 23 students selected through purposive random sampling. The instrument used was a kangkang jump skill assessment test. Data analysis was conducted using a normality test, which indicated that the pretest data (sig = 0.305) and posttest data (sig = 0.27) were normally distributed. A homogeneity test was conducted with sig = 0.451, and a paired sample t-test hypothesis test showed significant results with sig = 0.00. The results of the study demonstrated that the application of a game-based approach in learning significantly improved students' kangkang jumping skills. Future research on learning the kangkang jump can be conducted by integrating technology as an innovation of the Industrial Revolution 4.0.